2020
DOI: 10.1007/s10948-020-05438-w
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of Superfluidity Using the Berry Connection for Many-Body Wave Functions

Abstract: We show that two phenomena of superfluidity, superfluidity of weakly interacting bosons and superconductivity of the BCS model, are unified using the collective mode arising from the Berry connection for many-body wave functions. The superfluidity is attributed to the presence of this mode, which is stabilized by the interaction between particles that causes fluctuations of the number of particles participating in it. It is suggested that the existence of this collective mode and its stabilization is more fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…It is shown to be identified as A fic . According to our previous work [30], A MB is stabilized by the electron-pairing, meaning that the A fic is stabilized by the electron-pairing; thus, a stable nontrivial A fic necessary fo superconductivity is realized. In Section 6, we succinctly summarize part of our previous work that utilizes the particle-number fixed version of the BCS ground state [30], and conclude the present work by discussing implications for it.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…It is shown to be identified as A fic . According to our previous work [30], A MB is stabilized by the electron-pairing, meaning that the A fic is stabilized by the electron-pairing; thus, a stable nontrivial A fic necessary fo superconductivity is realized. In Section 6, we succinctly summarize part of our previous work that utilizes the particle-number fixed version of the BCS ground state [30], and conclude the present work by discussing implications for it.…”
Section: Introductionmentioning
confidence: 86%
“…Motivated by the above developments, we have reinvestigated the superfluidity problem in general [30]. Then, we have found that the particle number non-fixed formalism, such as the standard BCS formalism or the Bogoliubov-de Gennes formalism [31,32], can be cast in a particle number fixed formalism if the Berry connection is employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some recent studies [32][33][34][35][36], the shortcomings of the standard Eliashberg formalism in explaining some of the fundamental observation related to unconventional superconductivity has been highlighted and alternative formulation for a better theory is proposed. While our particle-particle ladder approximation does not use the standard Eliashberg formalism, it is an important task for future efforts, also for our own approach, to see how these proposed formulations can be adapted for better description of unconventional superconductivity.…”
Section: Methodsmentioning
confidence: 99%
“…In both cases, in the end, it is possible to describe the superconductor with a 3-band model [25]. For completeness, it is necessary to mention an alternative approach to explain the superconductivity in the iron pnictides based on the appearance of the nontrivial Berry connection [30][31][32].…”
Section: The Modelmentioning
confidence: 99%